2017
DOI: 10.1017/cem.2017.318
|View full text |Cite
|
Sign up to set email alerts
|

P116: A scoping review of factors affecting patient satisfaction with care in North American adult emergency departments

Abstract: was reached to include 18 of the 60 applications in a PEM fellowship curriculum and to exclude 2 applications from a PEM fellowship curriculum. Eighty-two percent (37 /45) of the experts completed Round 2 where 40 items were rated; consensus was reached to include 3 additional applications and exclude 5 applications. The decision was made not to carry on with future rounds after this stage, since no significant changes were observed between the two rounds, with regard to items that had not reached consensus. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Different study findings revealed that the relevance of information services given for patients, proper admitting processes, short waiting time to receive service, and ensuring privacy and confidentiality for services provided by the hospital had statistical association in other studies. On the other hand, different literatures also indicate that quality of communication and interpersonal skills is also the key indicator for patient satisfaction [13][14][15][16][17][18][19][20]. But none of the variables were found to be significant for patient satisfaction in our study.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Different study findings revealed that the relevance of information services given for patients, proper admitting processes, short waiting time to receive service, and ensuring privacy and confidentiality for services provided by the hospital had statistical association in other studies. On the other hand, different literatures also indicate that quality of communication and interpersonal skills is also the key indicator for patient satisfaction [13][14][15][16][17][18][19][20]. But none of the variables were found to be significant for patient satisfaction in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Various dimensions of patient satisfaction have been identified, health care services ranging from admission to discharge process, waiting time to receive care, as well as from medical care to interpersonal communication [13][14][15][16]. It has also been reported that the interpersonal and technical skills of health care provider are the two unique dimensions involved in a patient assessment of hospital care [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is a multidimensional aspect where patients’ perceptions and attitudes shape their overall health care–seeking experience [ 18 , 19 ]. Several factors, including registration time and process, waiting time to obtain health care services, interpersonal communication, and availability of basic amenities within health care facilities, can influence patient satisfaction with health care services [ 20 - 23 ]. Increased utilization and satisfaction of any insurance scheme are associated with improved quality of health care services.…”
Section: Introductionmentioning
confidence: 99%
“…Patient experiences include many dimensions such as waiting time, care from admission to discharge and communication between patient and health team 4 5. The technical and interpersonal skills of the health team were two core elements included in the patient appraisal to hospital services in Cameroon 6.…”
Section: Introductionmentioning
confidence: 99%